The Church and Education: Anglican Attitudes 1902 - Pugh, D. R. (The journal of ecclesiastical history, 1972)
As is well known, the Balfour Education Act of 1902 was the subject of bitter and prolonged controversy between Anglicans and Nonconformists. Ever since 1870 the Church schools had been struggling in unequal competition against the rate-aided School Board system, and many of them by the turn of the century were ‘dragging along a miserable existence’ with inadequate buildings and inadequate staff. Yet, believing their schools to be vital for their Church's survival, Anglicans hung on grimly, hoping that the Unionist government of Lord Salisbury would at last provide its long-promised succour. Fundamentally Anglicans were concerned not just for denominational teaching, but for the presentation of such teaching in a suitable atmosphere. ‘The necessity of a religious temper in teaching religion’ meant the subjection of teachers to religious tests and the retention of denominational control of the schools.